2021
DOI: 10.2106/jbjs.cc.20.00778
|View full text |Cite
|
Sign up to set email alerts
|

Medial Clavicle Fracture Fixation Including the Sternum

Abstract: Case: A 29-year-old man presented with a displaced medial clavicle fracture. Surgical repair was performed using a precontoured plate designed for the contralateral distal clavicle, and medial fixation was accomplished at the sternum. The patient had no complications and demonstrated full strength and range of motion at the 8-month follow-up. Conclusion: Medial clavicle fractures with a small medial fragment can be immobilized using a plate designed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…When the medial clavicle fragment is small or very comminuted and fixation is of concern, hook plates, 5 , 8 , 38 bridging plates to the sternum 12 , 26 , 39 and double-plating techniques 9 , 15 , 40 have been utilized to minimize the risk of fixation failure in multiple studies. However, despite high satisfaction and union rates, such fixation modalities typically require later removal.…”
Section: Discussionmentioning
confidence: 99%
“…When the medial clavicle fragment is small or very comminuted and fixation is of concern, hook plates, 5 , 8 , 38 bridging plates to the sternum 12 , 26 , 39 and double-plating techniques 9 , 15 , 40 have been utilized to minimize the risk of fixation failure in multiple studies. However, despite high satisfaction and union rates, such fixation modalities typically require later removal.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, fixation was limited to the medial clavicle and the authors reported rigid fixation, the lack of a plate removal due to less soft tissue irritation, and avoidance of damage to nearby structures given ability for placement of the reversed distal clavicle plate on the superior aspect of the medial clavicle. Schultz et al 15 also described a case of a displaced MCF; however, achieved adequate fixation with a contralateral distal clavicle plate across the SC joint. They found that the precontoured plate designed for the contralateral distal clavicle closely resembled the anatomy of the medial clavicle and SC joint and allowed for ease of placement.…”
Section: Discussionmentioning
confidence: 99%
“…Fixation of the medial clavicle with a reversed or contralateral distal clavicle plate has produced good outcomes in cases without nonunion. 15 , 19 Notably, Schultz et al 15 described acute fixation of a MCF utilizing a contralateral distal clavicle plate across the SC joint. The purposes of this retrospective study are to describe a similar technique; however, using a reversed distal clavicle locking plate for fixation across the SC joint, and to also report the functional and pain outcomes of this surgery for patients with symptomatic nonunion of MCFs.…”
mentioning
confidence: 99%